Algoritma Caesar Cipher atau Vigenere Cipher pada Pengenkripsian Pesan Teks - Vara Maulidyah Hidayah; Dadang Iskandar Mulyana; Yuliana Bachtiar (Departement of Mathematics Education, 2023)
Cryptography is a science that studies information security on data with the aim of preventing other people from wanting to know its contents, by using certain codes and rules and other methods so that only authorized people can see the contents of the code. By creating an application which uses the Java programming language with NetBeans to maintain the security of text input information sent by someone so that it is not easy to read, confidential text. The caesar algorithm is a classic substitution-based cipher system that is simple in encryption and decryption of a caesar cipher system using shift operations. The Vigenere Cipher algorithm is a classic cryptographic algorithm that utilizes the vigenere square principle to perform encryption.